Correlation of sinonasal anatomical variations with relevant sinus involvement in chronic rhinosinusitis: a prospective observational study - Chauhan, Priyanka; Bhat, Nalini; Bhandarkar, Pallavi; Singh, Ankita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The purpose of this study was to study the association of anatomical variations as risk factors in affecting specific sinuses in cases of chronic rhinosinusitis (CRS). Methods: It is an observational study carried out from June 2018 to May 2019. 61 patients of CRS were included in this study. The diagnosis of CRS with or without nasal polyposis was made as per diagnostic guidelines of the task force on chronic rhinosinusitis. Each of them was assessed by nasal endoscopy and computed tomography (CT) imaging for diagnosis and evaluation of anatomical risk factors. Results: A total of 61 patients of CRS were examined. Presence of various anatomical variants in relation to CRS were studied. We studied CT paranasal sinuses of the 61 patients, since each patient has 2 of each groups of sinuses, a total 122 group of sinuses are assessed in this study. On analyzing, we found, a significant association between deviated nasal septum (DNS) and maxillary sinusitis. Agger nasi cell and frontal and ethmoid (anterior and posterior) sinusitis, concha bullosa and maxillary sinusitis and over pneumatized ethmoid bulla and anterior and posterior ethmoid sinusitis. Other anatomical variants encountered, had no significant association with diseased sinuses (p value >0.01). Conclusions: The study showed that, there is a strong relationship between the presence of diseased sinus and some anatomical variants. It is suggested that besides anatomical variations, other clinical parameters should also be taken into account for the etiology of sinusitis.